Strategies for microbial decontamination of fresh blueberries and derived products (2020)
Increasing consumption of blueberries is associated with appreciation of their organoleptic properties together with their multiple health benefits. The increasing number of outbreaks caused by pathogenic microorganisms associated with their consumption in the fresh state and the rapid spoilage of this product which is mainly caused by moulds, has led to the development and evaluation of alternatives that help mitigate this problem. This article presents di erent strategies ranging from chemical, physical and biological technologies to combined methods applied for microbial decontamination of fresh blueberries and derived products. Sanitizers such as peracetic acid (PAA), ozone (O3), and electrolyzed water (EOW), and physical technologies such as pulsed light (PL) and cold plasma (CP) are potential alternatives to the use of traditional chlorine. Likewise, high hydrostatic pressure (HHP) or pulsed electrical fields (PEF) successfully achieve microbial reductions in derivative products. A combination of methods at moderate intensities or levels is a promising strategy to increase microbial decontamination with a minimal impact on product quality.